2008
DOI: 10.1159/000132410
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B Receptors on Vascular Smooth Muscle Cells of the Human Umbilical Vein Mediate Vasoconstriction

Abstract: Objective: To test the hypothesis that smooth muscle cells of the human umbilical vein have vasoconstricting endothelin B (ETB) receptors. Methods: In strip preparations of human umbilical veins isometric tension after exposure to the selective ETB receptor agonist sarafotoxin S6c (S6c) was compared to the tension before S6c exposure (set as 100%). Results: In intact preparations S6c induced vasoconstriction only at the highest concentration applied (10–8M; 149.5 ± 12.5 vs. 100%, p < 0.05). In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In the present study, only contractile responses were observed when the vessels were activated by ET‐1 and sarafotoxin S6a. A similar finding has been reported in several studies of endothelium‐intact human vessels including the internal mammary artery and vein (Seo et al, ), pulmonary artery (McCulloch et al, ), coronary artery (Holm and Franco‐Cereceda, ), umbilical vein (Mildenberger et al, ) and saphenous vein (White et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, only contractile responses were observed when the vessels were activated by ET‐1 and sarafotoxin S6a. A similar finding has been reported in several studies of endothelium‐intact human vessels including the internal mammary artery and vein (Seo et al, ), pulmonary artery (McCulloch et al, ), coronary artery (Holm and Franco‐Cereceda, ), umbilical vein (Mildenberger et al, ) and saphenous vein (White et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…It is thought that the endothelial ET B R counteracts the constrictor effects of ET-1 to maintain vascular homeostasis (30). Furthermore, loss of ET B R on the venous endothelium can augment vasoconstrictor response to venous smooth muscle ET B R activation (25). A shift in the ratio of endothelial to smooth muscle ET B R expression and a decrease in ET B R-mediated NO production have been previously demonstrated in animal models with risk factors for cardiovascular disease (20).…”
Section: Discussionmentioning
confidence: 96%
“…Studies in other systems with EDN receptor antagonists support a role for EDNRB, and not EDNRA, in regulating vascular tone (Schneider et al, 2007). EDNRB when activated by sarafotoxin S6c induces intense contractions in human umbilical vein smooth muscle cells, indicating a role in regulating vascular tone (Mildenberger et al, 2008). Collectively, EDNmediated vasoconstriction following progesterone withdrawal is likely facilitated preferentially through EDNRB.…”
Section: Endothelins In the Macaque Endometriummentioning
confidence: 99%